2014
DOI: 10.1519/jsc.0000000000000512
|View full text |Cite
|
Sign up to set email alerts
|

Body Fat has No Effect on the Maximal Fat Oxidation Rate in Young, Normal, and Overweight Women

Abstract: The purpose of this study was to examine how fat mass affects the maximal fat oxidation rates of women. Fourteen active, healthy women (age, 21-31 years) with body composition ranging from 18.6 to 30.0% fat were divided into 2 groups (15-24.9% = lower-fat group; 25-35% = higher-fat group). On day 1, subjects performed a graded exercise test on the treadmill to determine maximal oxygen consumption (VO2max). On day 2, subjects were measured for % fat and performed a maximal fat oxidation test. Fat and carbohydra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 17 publications
3
12
2
Order By: Relevance
“…On the other hand, the results of the present study differ with previous investigations performed on recreationally active overweight and lean subjects where MFO was not associated with body fatness [ 15 , 16 , 17 ]. Differences in the participants’ sex, body composition, physical activity level and experimental design, hinders comparison among studies result.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…On the other hand, the results of the present study differ with previous investigations performed on recreationally active overweight and lean subjects where MFO was not associated with body fatness [ 15 , 16 , 17 ]. Differences in the participants’ sex, body composition, physical activity level and experimental design, hinders comparison among studies result.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, the sample size of the present study is similar to previous studies analyzing the association of MFO and body fatness (sample size range 14–54) [ 15 , 16 , 17 ], nonetheless, future large-cohort studies are needed to corroborate the here reported associations.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Mannaing et al [40]. claimed that the initial level of blood lipids, being non-obese or the level of fat storage Blaize et al [41] may lead to the effectiveness of an exercise program that result in significant changes in blood lipid profiles. Therefore, in our study the activity level of the participants in 3 to 4 sessions of leisure activity per month, low sample size and duration of exercise program are limitations of the present study, and may be the reason that the measures of fatness other than fat % did not change significantly.…”
Section: Discussionmentioning
confidence: 99%